Siklus Bisnis Perekonomian Indonesia di Masa Pandemi Covid-19 - Teguh Warsito (Publikasi Indonesia, 2023)
The Covid-19 pandemic has become one of the biggest shocks to the Indonesian economy. As a result of the pandemic, there was deep pressure on aggregate demand and aggregate supply as well, so the economic output decreased and was not at optimal output levels. This paper will show the business cycle or economic fluctuations that occurred during the Covid-19 pandemic. The method used in this paper is the decomposition of Indonesia's quarterly real GDP for the 2000-2022 period into the growth trend and short-term fluctuations using the Hodrick–Prescott (HP) Filter. The results of this study indicate that in the first quarter of 2020, Indonesia experienced an economic contraction and was followed by a recession in the following quarter. After that, economic recovery occurred and reached long-term optimal output after 1.5 years. The characteristics of a recession and economic recovery followed a W-Shaped due to new pressures during the recovery process caused by the Delta variant, so a new recession occurred. By looking at the business cycle of the economy, the government can implement appropriate policies both fiscal and monetary at each phase.